2014
DOI: 10.1016/j.athoracsur.2014.06.059
|View full text |Cite
|
Sign up to set email alerts
|

Readmissions After Cardiac Surgery: Experience of the National Institutes of Health/Canadian Institutes of Health Research Cardiothoracic Surgical Trials Network

Abstract: Background Readmissions are a common problem in cardiac surgery. The goal of this study was to examine the frequency, timing, and associated risk factors for readmission after cardiac surgery. Methods 5,158 adult cardiac surgery patients (5,059 included in analysis) were prospectively enrolled in a 10center cohort study to assess risk factors for infection following cardiac surgery. Data were also collected on all-cause readmissions occurring within 65 days after surgery. Major outcomes included readmission … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
85
5
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(117 citation statements)
references
References 20 publications
11
85
5
5
Order By: Relevance
“…Our 30‐day rehospitalization rate for a mixture of cardiac surgery operations for the entire patient population (not just prICULOS patients) postdischarge was 11.7%. This is in keeping with the published literature, which generally consists of large studies (thousands of patients) from multiple hospitals in the United States where 30‐day rehospitalization rates (mostly post CABG) average about 5% to 12% with the range being 0% to 80% . Our 90‐day rehospitalization rate of 17.2% (Figure ) is also comparable to the published results from Iribarne et al, who reported 65‐day rehospitalization rates (from index operation) among 10 centers with 5158 adult cardiac surgical patients at 18.7%.…”
Section: Discussionsupporting
confidence: 91%
“…Our 30‐day rehospitalization rate for a mixture of cardiac surgery operations for the entire patient population (not just prICULOS patients) postdischarge was 11.7%. This is in keeping with the published literature, which generally consists of large studies (thousands of patients) from multiple hospitals in the United States where 30‐day rehospitalization rates (mostly post CABG) average about 5% to 12% with the range being 0% to 80% . Our 90‐day rehospitalization rate of 17.2% (Figure ) is also comparable to the published results from Iribarne et al, who reported 65‐day rehospitalization rates (from index operation) among 10 centers with 5158 adult cardiac surgical patients at 18.7%.…”
Section: Discussionsupporting
confidence: 91%
“…Nevertheless, unscheduled re-admissions after hospital discharge remain a persistent clinical challenge. The 30-day re-admission rate after CABG is 15e20%, and is an important cause of prolonging recovery, patient dissatisfaction and escalating medical costs [18,27,28]. To our knowledge, this is the first study to evaluate the effects of sleep apnoea on unscheduled re-admissions after CABG.…”
Section: Discussionmentioning
confidence: 90%
“…To our knowledge, the only prospective multi‐center study of chart‐level data with respect to causes of readmission after cardiac surgery comes from The Cardiothoracic Surgical Trials Network, which examined all‐cause readmissions occurring within 65 days of cardiac surgery for 5158 adults across 10 centers . The overall rate of readmission was 18.7% and the primary causes of admission were infection (17.1%), arrhythmia (17.1%), and volume overload (13.5%).…”
Section: Discussionmentioning
confidence: 99%